ISO 13485 : a complete guide to quality management in the medical device industry - Abuhav, Itay (Boca Raton : CRC Press, 2012)
'The United States and European Union now require the ISO 13485 Standard certification for medical device manufacturers. Written by an experienced industry professional, this practical book provides a complete guide to the ISO 13485 standard certification for medical device manufacturing in terms of quality control. It covers all the requirements of ISO 13485 and offers a step-by-step comparison between the ISO 13485 and ISO 9001, enabling a sound understanding of these new procedures'--Provided by publisher.
Scope -- Normative references -- Terms and definitions -- Quality management system -- Management responsibility -- Resource management -- Product realization -- Measurement, analysis, and improvement.
Includes index.
Includes bibliographical references and index.
Keywords: Medical instruments and apparatus -- Standards -- Handbooks, manuals, etc; Medical instruments and apparatus industry -- Quality control -- Standards -- Handbooks, manuals, etc; Equipment and Supplies -- standards; Equipment Design -- standards; Manufactured Materials -- standards; Quality control; Equipement mico-chirurgical.; Normes internationales; ISO; Contr{u3BEC}e de qualit{u296E}; Manuels